2022
DOI: 10.2147/copd.s380736
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal Peak Inspiratory Flow and Critical Inhalation Errors are Associated with Higher COPD-Related Healthcare Costs

Abstract: Purpose To assess the relationship between suboptimal Peak Inspiratory Flow (sPIF), inhalation technique errors, and non-adherence, with Healthcare Resource Utilisation (HCRU) in Chronic Obstructive Pulmonary Disease (COPD) patients receiving maintenance therapy via a Dry Powder Inhaler (DPI). Patients and methods The cross-sectional, multi-country PIFotal study included 1434 COPD patients (≥40 years) using a DPI for maintenance therapy. PIF was measured with the In-Che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…1091 abstracts were eliminated, leaving 55 full-text articles for review in detail. Among these articles, 36 did not contain information about associations between errors and outcomes or were review articles, resulting in a total of 19 publications that were included in this review5 11–28 (table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1091 abstracts were eliminated, leaving 55 full-text articles for review in detail. Among these articles, 36 did not contain information about associations between errors and outcomes or were review articles, resulting in a total of 19 publications that were included in this review5 11–28 (table 1).…”
Section: Resultsmentioning
confidence: 99%
“…10 retrospective case–controlled studies, reported in 12 publications, compared the characteristics of patients who made and who did not make errors using their inhalers (table 1). 5 12 14 15 17 18 20 22 23 25 27 28 These included larger numbers of patients than the prospective studies. Three publications23 27 28 reported different outcomes from the same study (The PIFotal COPD study).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A cross-sectional, multicountry study by Leving et al [8 ▪ ] including COPD patients using a DPI for maintenance therapy found that sPIF and inhalation technique errors were associated with higher COPD-related healthcare utilization and costs. PIF was measured with the In-Check DIAL G16, and sPIF was defined as a typical PIF lower than required for the device, which ranged from 15 to 60 l/min according to the DPI.…”
Section: Why Is Peak Inspiratory Flow Important?mentioning
confidence: 99%
“…The PIFotal study revealed that inhalation technique errors were common and associated with worse health status 2 . In addition, a higher cumulative number of inhalation technique errors was associated with higher COPD-related healthcare costs 9 . These findings highlight the importance of correct DPI handling in managing COPD.…”
Section: Introductionmentioning
confidence: 99%